Primary health‐care nurses and Internet health information‐seeking: Access, barriers and quality checks. Issue 1 (30th October 2014) - Gilmour, Jean; Strong, Alison; Chan, Helen; Hanna, Sue; Huntington, Annette
Abstract : Online information is a critical resource for evidence‐based practice and patient education. This study aimed to establish New Zealand nurses' access and evaluation of online health information in the primary care context using a postal questionnaire survey; there were 630 respondents from a random sample of 931 nurses. The majority of respondents were satisfied with work access to online information (84.5%, n = 501) and searched for online information at least several times a week (57.5%, n = 343). The major barrier to online information seeking was insufficient time, but 68 respondents had no work online information access. The level of nursing qualification was significantly correlated with computer confidence and information quality checking. A range of information evaluation approaches was used. Most nurses in study accessed and evaluated Internet information in contrast to the findings of earlier studies, but there were barriers preventing universal integration into practice.